Management of patients with placenta accreta spectrum disorders who underwent pregnancy terminations in the second trimester: A retrospective study. (November 2019) - Ou, Jie; Peng, Ping; Teng, Lirong; Li, Chunying; Liu, Xinyan
Abstract: Purpose: To analyse the management of patients with placenta accreta spectrum (PAS) disorders who underwent 2 nd trimester pregnancy terminations. Method: The records of patients with PAS disorders who underwent 2 nd trimester pregnancy terminations were collected and analysed. Results: Twenty-eight patients were included; 8 (28.6%) patients received prenatal diagnoses and 20 (71.4%) patients received postnatal diagnoses. In the prenatal diagnosis group, scheduling hysterotomy and placenta removal were performed in 5 patients with complete placenta previa and previous caesarean delivery without hysterectomy or postpartum haemorrhage, and medical termination was performed in 3 patients, 2 of whom retained the placenta in situ. In the postnatal diagnosis group, the placenta remained in situ in 11 patients, and in 13 (46.4%) patients overall, adjuvant treatments were applied to the patients, and the abnormally implanted placenta was passed 43.5 (range: 7–102) days after termination. A complication associated with the placenta left in situ included intrauterine infection in one case. Uterus preservation was achieved in all the patients. Conclusions: For patients with PAS disorders with complete placenta previa and previous caesarean delivery, hysterotomy is a safe choice for terminating a 2 nd trimester pregnancy. When it is impossible to manually remove the placenta, leaving the placenta in situ with the administration of adjuvant treatment is a good choice for uterus preservation.